Drinking frequency modifies an association between salt intake and blood pressure: A cohort study. Issue 4 (16th March 2020) - Yoshimura, Ryuichi; Yamamoto, Ryohei; Shinzawa, Maki; Tomi, Ryohei; Ozaki, Shingo; Fujii, Yoshiyuki; Ito, Takafumi; Tanabe, Kazuaki; Moriguchi, Yasuaki; Isaka, Yoshitaka; Moriyama, Toshiki
Abstract: Salt sensitivity is one of the crucial risk factors of hypertension. The aim of the present prospective cohort study was to assess the clinical impact of alcohol drinking on an association between salt intake and blood pressure. The present study included 451 employees at a pharmaceutical company in Japan who underwent annual health checkups in both 2017 and 2018. The main exposure of interest was self‐reported drinking frequency at their first checkups: rarely, occasionally, and daily. To assess the association between the change of salt intake estimated from single‐spot urine specimens and that of blood pressure, the differences in systolic/diastolic blood pressure and salt intake between 2017 and 2018 were calculated for each subject. Multivariable‐adjusted linear regression models adjusting for clinically relevant factors clarified a drinking frequency‐dependent association between Δsalt intake and Δsystolic blood pressure (per 1 g/d of Δsalt intake adjusted β [95% confidence interval] 0.19 [−0.73, 1.12], 0.84 [0.14, 1.53], and 1.78 [0.86, 2.69] in rare, occasional, and daily drinkers). A similar association between Δsalt intake and Δdiastolic blood pressure was also observed (−0.24 [−1.02, 0.54], 0.67 (0.18, 1.16), 0.95 [0.38, 1.51], in rare, occasional, and daily drinkers). The interactions between drinking frequency and Δsalt intake were found to be statistically significant ( P for interaction = .028 and .006 for ∆systolic blood pressure and ∆diastolic blood pressure, respectively). The present study identified enhanced salt sensitivity in the subjects who drink at a higher frequency, suggesting that the reduction in alcohol consumption may improve salt sensitivity in higher frequency drinkers.